Psychopathological outcomes of adolescent borderline personality disorder symptoms. (March 2020) - Winsper, Catherine; Wolke, Dieter; Scott, Jan; Sharp, Carla; Thompson, Andrew; Marwaha, Steven
Objective: Despite considerable morbidity and functional losses associated with adolescent borderline personality disorder, little is known about psychopathological outcomes. This study examined associations between adolescent borderline personality disorder symptoms and subsequent depressive, psychotic and hypomanic symptoms. Methods: We used data from the Avon Longitudinal Study of Parents and Children. Participants were adolescents living in the community who had data for all longitudinal outcomes ( N = 1758). We used logistic regression and path analysis to investigate associations between borderline personality disorder (five or more probable/definite symptoms) reported at age 11–12 years and depressive and psychotic symptoms reported at age 12 and 18, and lifetime hypomanic symptoms reported at age 22–23 years. Results: Adolescent borderline personality disorder symptoms were associated with psychotic symptoms (odds ratio: 2.36, confidence interval: [1.82, 3.06]), diagnosis of depression at age 18 years (odds ratio: 1.30, confidence interval: [1.03, 1.64]) and hypomanic symptoms (odds ratio: 2.89, confidence interval: [2.40, 3.48]) at 22–23 years. Path analysis controlling for associations between all outcomes indicated that borderline personality disorder symptoms were independently associated with depressive symptoms (β = 0.97, p < 0.001) at 12 years and hypomanic (β = 0.58, p < 0.01) symptoms at 22–23 years. Borderline personality disorder symptoms were also associated with psychotic symptoms at age 12 years (β = 0.58, p < 0.01), which were linked (β = 0.34, p < 0.01) to psychotic symptoms at age 18 years. Conclusion: Adolescents with borderline personality disorder symptoms are at future risk of psychotic and hypomanic symptoms, and a diagnosis of depression. Future risk is independent of associations between psychopathological outcomes, indicating that adolescent borderline personality disorder symptoms have multifinal outcomes. Increasing awareness of borderline personality disorder in early adolescence could facilitate timely secondary prevention of these symptoms subsequently, helping to prevent future psychopathology.